Genomic analysis reveals genetic diversity and selection signatures of the Yantai Black pig during domestication and breeding - Qin, Ming; Ma, Cai; Liang, Mingzhi; Zhang, Yuxin; Wang, Zengguang; Wang, Jingyu; Li, Guodong; Sha, Yufen; Jin, Peng; Ju, Lingling; Liu, Xueping; Zeng, Yongqing; et al. (Frontiers in Genetics, 2025)
ObjectiveYantai Black pig (YT), as a native population of the eastern China’s Jiaodong Peninsula of Shandong province, characterized by coarse feeding tolerance, strong disease resistance, early sexual maturity, high litter size, and superior meat quality. However, the genetic characteristics and variations underlying its crucial economic traits remain poorly understood.MethodsIn this study, we resequenced the whole genome of 17 YT individuals from distinctly different lineages breeding in three conservation farms to detect single nucleotide polymorphism (SNP) density, pairwise fixation index (FST), nucleotide diversity (π), runs of homozygosity (ROHs).ResultsOur findings revealed that YT has higher genomic diversity compared to Chinese partial indigenous pig populations and Western commercial pig populations, but lower diversity than Asian wild boars (AWB). Based on FST and values (top 1%), we identified 321 selected regions, encompassing 156 genes, between YT and AWB. Functional annotation analysis suggested that these genes are potentially responsible for growth, reproduction, and immune responses. The RBFOX3 and WDR27 genes were confirmed to be strong positively selected in YT’s breeding. Combining the results of selection sweeps and ROH islands of YT, three overlapping regions were detected. Furthermore, we found that the quantitative trait loci (QTLs) with the most overlapping regions were related to teat number, body weight, and mean corpuscular hemoglobin concentration.ConclusionWe characterized the genomic features and population structure and identified selection signals in genomic regions linked to important germplasm characteristics of YT. The insights gained from this study provide valuable references and a solid foundation for the preservation, breeding, and utilization of YT and its valuable genetic resources.